Comparison of Perioperative Complications in Anterior Decompression With Fusion and Posterior Decompression With Fusion for Cervical Ossification of the Posterior Longitudinal Ligament: Propensity Score Matching Analysis Using a Nation-Wide Inpatient Database. Issue 16 (15th August 2020) - Yoshii, Toshitaka; Morishita, Shingo; Inose, Hiroyuki; Yuasa, Masato; Hirai, Takashi; Okawa, Atsushi; Fushimi, Kiyohide; Fujiwara, Takeo
Abstract : Study Design: A retrospective comparative study. Objective: To compare the perioperative complications and costs of anterior decompression with fusion (ADF) and posterior decompression with fusion (PDF) for patients with cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: Surgical treatment of cervical OPLL has a high risk of various complications. ADF and PDF are effective for the treatment of cervical OPLL; however, few studies have compared the two procedures in terms of the perioperative surgical complications. Methods: Patients undergoing ADF and PDF for cervical OPLL from 2010 to 2016 were identified in a nation-wide inpatient database. We investigated systemic and local complications, length of hospital stay, costs for hospitalization, reoperation, and mortality. Propensity score was calculated from patients' characteristics and preoperative comorbidities, and one to one matching was performed. Results: Propensity score-matching produced 854 pairs of patients who underwent ADF and PDF. The rate of at least one systemic complication was significantly higher in the ADF group ( P = 0.004). The incidence rates of postoperative respiratory failure ( P = 0.034) and dysphagia ( P = 0.008) were significantly higher in the ADF group. The rates of pneumonia ( P = 0.06) and hoarseness ( P = 0.08) also tended to be higher in the ADF group. However, no difference was found in the mortality rate ( P = 0.22). In the local complications, spinal fluid leakage was significantly higher in the ADF group ( P < 0.001). However, blood transfusion rate was significantly higher in the PDF group ( P = 0.001). Hospital stay was significantly longer in the PDF group ( P < 0.001) and the cost for hospitalization was greater in the PDF group ( P < 0.001). Conclusion: The present study demonstrated that perioperative complications, such as respiratory failure, dysphagia, and spinal fluid leakage, were more common in the ADF group. However, hospital stay was longer in the PDF group, and the cost for hospitalization was greater in the PDF group. Level of Evidence: 3. Abstract : Propensity matching analysis comparing perioperative complications after anterior decompression with fusion (ADF) and posterior decompression with fusion (PDF) was conducted using a large national database, which demonstrated that respiratory failure, dysphagia, and spinal fluid leakage were more common in the ADF group. However, the rate of transfusion and cost for hospitalization was higher in the PDF group.